On Fundamental Group of a Certain Class of Welded Knots (Communications in Mathematical Research, 2019)
In this paper, a certain class of welded knots $K_{2n}$ is considered. By calculating the commutators subgroup of fundamental group $G_n$ of welded knot $K_{2n}$, $n ∈$ Z+, we show that these welded knots are not equivalent to each other and they are all not classical knots. Secondly, we study some properties of $G_n$ and obtain that $G_n$ is linear, residually finite and Hopfian.